The simulator sickness questionnaire, and the erroneous zero baseline assumption - Brown, Phillip; Spronck, Pieter; Powell, Wendy (Frontiers in Virtual Reality, 2022)
Cybersickness assessment is predominantly conducted via the Simulator Sickness Questionnaire (SSQ). Literature has highlighted that assumptions which are made concerning baseline assessment may be incorrect, especially the assumption that healthy participants enter with no or minimal associated symptoms. An online survey study was conducted to explore further this assumption amongst a general population sample (N=93). Results for this study suggest that the current baseline assumption may be inherently incorrect.